Watch my baby grow follow one baby's first year - and find out how your baby thinks and feels - Bhattacharya, Shaoni; Emma; Hall, Sally J; Holmstrom, Radhika (2015)
"By following the journey of one child and her family, Watch My Baby Grow looks at a baby's developing abilities, from birth, over the course of a year. In the light of new scientific knowledge, this book explores every area of a baby's progress, and provides a fascinating insight into what it's really like from a baby's point of view."--Book jacket
Includes index
1
Keywords: Child rearing; Infants -- Care; Infants -- Development; Mother and infant